Did the sweetness of beverages change with the Chilean Food Labeling and Marketing Law? A before and after study - Rebolledo, Natalia; Bercholz, Maxime; Corvalán, Camila; Ng, Shu Wen; Taillie, Lindsey Smith (Frontiers in Nutrition, 2022)
There has been a rapid proliferation of policies around the globe to reduce sugar consumption, yet there is little understanding as to whether these policies have led to changes in the overall sweetness of products, which is essential for understanding long-term effects on food preferences and intake. For example, the implementation of Chile's Law on Food Labeling and Advertising led to decreases in the sugar content of nonalcoholic packaged beverages and increases in nonnutritive sweeteners (NNS) use in these beverages. Given that NNS have greater sweetness intensity than sugars, it is unclear what was the net effect of these changes on the sweetness of purchased beverages. Using longitudinal household purchase data (n>2000 households), we measured the changes in the sweetness of beverage purchases after implementing the first phase of the Chilean law and examine if there were differences by key family sociodemographic variables. We developed three sweetness indices: 1) NNS sweetness, including the sweetness of the six NNS most consumed by Chileans; 2) total sugars sweetness, including the sweetness from total sugars; and 3) total sweetness, combining the sweetness from NNS and sugars. Using fixed-effects models, we compared the observed post-law purchases to a counterfactual based on pre-law trends. We found that NNS sweetness increased relative to the counterfactual, while total sugars sweetness decreased after the law. However, the absolute changes in NNS sweetness were almost entirely offset by the decreases in total sugar sweetness, leading to no change in the total sweetness of beverage purchases. Additionally, there were no differences in the sweetness changes by family sociodemographics. Our findings indicate that Chilean consumers are exposed to similar sweetness levels in their beverages after the law. Future research should explore whether sweetness also remained consistent in dietary intake.